A study of electrolyte imbalance in Coronavirus Disease-2019 at a rural tertiary health care center - R Sheeba; Dinesh Kumar Vishwanathan; Vasantha Kamath (Wolters Kluwer Medknow Publications, 2023)
Background: With the ongoing onslaught of coronavirus disease-2019 (COVID-19) pandemic, identifying factors predicting the disease course and outcome become immensely important. Although globally reported, a potential association between electrolyte disturbance and COVID-19 disease has not been well researched. Dyselectrolytemia not only impacts patient care but also provides insight into the pathophysiology of COVID-19. Aims and Objectives: Our aim was to study electrolyte disturbances among COVID-19 patients and its impact on the disease outcome. Materials and Methods: This was a retrospective observational study conducted in a total of 397 patients detected to have electrolyte abnormalities among 2914 adult inpatients, diagnosed with COVID 19 infection in a tertiary care center over a period of 10 months (July 2020-December 2020 and April 2021-July 2021). Results: A total of 2914 patients were diagnosed with COVID-19 of whom 397 (13.62%) patients were found to have an electrolyte imbalance. Hyponatremia (n = 199) 51% was the most common electrolyte disturbance followed by hypokalemia (n = 94) 24.3% and mixed electrolyte abnormality (n = 81) 20.4%. Electrolyte imbalance was directly related to the clinical outcome of the disease which was statistically significant P = 0.0001. Conclusion: Hyponatremia has a significant direct correlation with mortality in patients with COVID-19. However, hypokalemia, hyperkalemia, and hypernatremia also influence the disease outcome. We recommend that the estimation of electrolytes should be done routinely for all hospitalized patients with COVID-19 as it adds to the prognostication of these patients.